An in silico approach to the mechanical design of meta-materials for adipose tissue engineering - Emanuele Luigi Carniel; Chiara Giulia Fontanella; Maria Vittoria Mascolini; Sofia Pettenuzzo; Ilaria Toniolo; Alice Berardo (Heliyon)
Meta-materials are an innovative tool for engineering applications, made possible by advanced computational methods for designing meso-structural organization and additive manufacturing techniques that can produce meso-structures unattainable with traditional manufacturing methods. One significant application of meta-materials is in tissue engineering. They offer the capability to mimic tissue configurations at the meso-structural level and replicate mechanical properties, making them invaluable in this field.This work proposes a computational mechanics framework to characterize and parameterize the mechanical behavior of meta-materials that potentially can mimic the adipose tissue. The approach begins by identifying key parameters that define the mechanical response, followed by determining meso-structural factors that may influence these parameters. Computational analyses are then employed to quantify the influence of these factors on the parameters. The results obtained from these analyses form the basis for accurately identifying the meso-structural configuration of the meta-material, tailored to specific application requirements.A specific meta-material is proposed to replicate the meso-structural architecture and mechanical properties of adipose tissue, considering both compressive and indentation responses. The application of the computational procedure suggests the potential of the meta-material to be exploited as a scaffold for soft tissue engineering.